2014
DOI: 10.1590/0103-6440201302290
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Tensile Strength of Luting Cements on Metallic Substrate

Abstract: The aim of this study was to determine the tensile strength of crowns cemented on metallic substrate with four different types of luting agents. Twenty human maxillary molars with similar diameters were selected and prepared to receive metallic core castings (Cu-Al). After cementation and preparation the cores were measured and the area of crown's portion was calculated. The teeth were divided into four groups based on the luting agent used to cement the crowns: zinc phosphate cement; glass ionomer cement; res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
0
8
0
1
Order By: Relevance
“…Retention is an important factor in determining the success and clinical service of FPDs 1. The retention of crown is based on the presence of two almost parallel vertical surfaces from tooth preparation; Al-Omari et al suggested that the mean convergence angle between 22.4 and 25.3 degrees was clinically acceptable 2.…”
Section: Introductionmentioning
confidence: 99%
“…Retention is an important factor in determining the success and clinical service of FPDs 1. The retention of crown is based on the presence of two almost parallel vertical surfaces from tooth preparation; Al-Omari et al suggested that the mean convergence angle between 22.4 and 25.3 degrees was clinically acceptable 2.…”
Section: Introductionmentioning
confidence: 99%
“…GIC has low tensile strength and fracture resistance and the studies confirmed that it establishes no chemical bond with noble metal alloys. 2 28 45 46 However, it has been reported that the passive oxide layer formed on the surface increases the bond strength of glassionomer cements to base metal alloys. 47 These reports correlate with the results of our study.…”
Section: Discussionmentioning
confidence: 99%
“…The oxide layer formed over cp titanium produces a firm oxide adherent layer that does not influence the bond strength of self-adhesive resin cements (25). However, the bond strength of the cements varies depending on the prosthodontic substrate, indicating that selection of these cements should be dictated by the substrate (26) Certain properties of resin cements compared are superior to other types of cements, like greater fracture resistance (18,27,28), good adherence to dental structures and alloys provided by adhesive systems (29,30), low solubility in oral fluids, in addition to the reduced leakage in restorations (29), make the resin cements agents of choice for cementation. It is claimed that there is no established value of load considered ideal for clinical success of prosthesis retention (30).…”
Section: Discussionmentioning
confidence: 99%